Effectively protecting an area without internal frontiers within the EU? - Leitner, Ole (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2025)
The article analyses the VGH Munich judgment of 17 March 2025 (10 BV 24.700), the first German decision to declare Germany’s internal border controls at the German-Austrian border unlawful under EU law. It situates the case within the Schengen system, whose core achievement is the abolition of systematic controls at internal borders. Since 2015, however, several Member States have repeatedly reintroduced "temporary" controls, initially in response to the refugee crisis and later justified by terrorism, secondary migration and COVID-19, with some measures persisting for years. While the Schengen Borders Code (SBC) permits reintroduction only exceptionally and within strict time limits, Member States have increasingly exceeded those limits, and the Commission has largely refrained from enforcement, shifting the burden to individuals and national courts. The case arose from an identity check carried out as an internal border control in June 2022. The plaintiff, an Austrian academic who frequently crosses the border, sought a declaratory judgment that the check was unlawful. The VGH held the action admissible on the basis of a concrete risk of recurrence, rejecting arguments based on short-term expiry and finding the check not to be a "serious" rights infringement. Substantively, applying CJEU case law in NW, it held the SBC time limits to be absolute: controls become unlawful once they exceed the permitted duration unless a genuinely "new" serious threat is shown. Judicial review is limited to the reasons stated in the Article 25a notification. The judgment highlights both national courts’ enforcement role and the potential incompatibility of German admissibility rules with effective judicial protection under EU law.
Keywords: Evropska unija; migracije; migracijsko pravo; notranje mejne kontrole; prosto gibanje oseb; Sodišče EU; sodna praksa; sodno varstvo; strateško pravdanje; Zakonik o schengenskih mejah